2020
DOI: 10.1177/0030222820966248
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Palestinian and Polish Medical Students Towards Death

Abstract: Attitudes of students of health-related subjects towards the death are an important issue showing the behaviour and values ​​that guide young people in everyday interactions. The study was conducted using the Questionnaire About Attitudes Against Death (DAP-R-PL) among 309 students, including 150 Palestinian from the Faculty of Nursing and Health Sciences and 159 Polish from the Faculty of Health Sciences. It was noticed that the attitude of Death Avoidance is higher in Palestinians than in Poles. The biggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…It can be assumed that as a result of the outbreak of the pandemic, people have largely lost control of existential problems and feel insecure in the space of an unstable epidemiological situation. Similar results were observed in studies conducted among students who, as a result of the armed conflict with Israel, live in constant fear for their lives [13].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It can be assumed that as a result of the outbreak of the pandemic, people have largely lost control of existential problems and feel insecure in the space of an unstable epidemiological situation. Similar results were observed in studies conducted among students who, as a result of the armed conflict with Israel, live in constant fear for their lives [13].…”
Section: Discussionsupporting
confidence: 87%
“…The above thesis is confirmed by the results of other studies conducted in this matter [13,26,27]. The attitude of fear towards death negatively correlated with the neutral acceptance of death.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results of the current study showed that men HPs avoided less thoughts and conversations about death in order to reduce death anxiety (death avoidance) in contrast to women, a finding that is consistent with the study by Asadpour et al (2016) which was conducted on a sample of medical students, but disagrees with Malliarou et al (2011b) who studied Greek nurses that provided palliative care to adults. Also, our study supports that men HPs believed less in the existence of a happy afterlife (approach acceptance), which is in accordance with other studies (Gama et al, 2012; Zdziarski et al, 2020) but contradicts the findings of Malliarou et al (2011b), where men showed greater faith in a happy afterlife. It may be assumed that men in our study were probably under the influence of social stereotypes that want them strong and invulnerable in adversities, pushing them in a way to discuss death issues more comfortably.…”
Section: Discussionsupporting
confidence: 87%
“…In the available literature, medical and nursing staff often refer to death as a transition, which may suggest that life continues after death. The above opinion indicates an ethical approach to death, but above all a spiritual attitude and a religious view of this phenomenon [ 11 , 12 ]. The results of other studies conducted in the medical world, e.g., among Palestinian and Polish medical students, confirm the thesis that people preparing to work in medical services have a positive existential and religious attitude to death [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%